Biomechanics and energy demands - with focus on double poling - Holmberg, H. C. (4th International Congress on Science and Skiing, 2007)
Cross-country skiing is one of the most demanding endurance sports. During the last decade there has been an enhanced emphasize on upper body development which has markedly improved skiers endurance and muscle strength in their arm and torso region and capability to utilize a high fraction of VO2 max in different skiing techniques. These improvements demonstrates a high adaptive potential and that upper body muscles can adapt towards a similar level äs leg muscles in well-trained c,c. skiers, Moreover, novel biomechanical development with innovative modifications of skiing techniques has contributed to higher racing velocities, decisive for performance especially in the new sprint events and mass-start. One of the most important racing techniques is double poling (DP), a complex movement involving both the upper and lower body. In this technique the pole force is directly related to velocity and influenced by specific muscle activation patterns and a specific characteristic flexion-extension pattern in the elbow, hip, and knee joints, with the angle minima occurring around the peak pole force. The muscles are engaged in a sequential order starting with trunk and hip flexors, followed by shoulder extensors and the elbow extensor triceps brachii (Holmberg, 2005). The best skiers in DP use a strategy characterized by smaller joint angles, higher flexion velocities, and higher pole force applied during a shorter poling phase (Holmberg et al, 2005). In addition, a free dynamic motion of the legs during the movement has shown to be related to 1) a higher impulse of pole force and peak pole force, a longer recovery time during each poling cycle, and a lower poling frequency; 2) a lower heart rate response and blood lactate concentration, with no difference in oxygen consumption at submaximal velocities; 3) a higher peak oxygen uptake and maximal DP velocity; and 4) a longer time to exhaustion (Holmberg et al. 2006). Altogether, this Supports a functional importance involving the lower body to optimize DP performance. Future developments of the DP technique involve examination regarding the effect of different poling frequencies and anthropometrics characteristics on the physiological response and DP performance. To achieve a higher understanding the use of an integrative biomechanical and physiological approach is an important tool to add knowledge to enable further improvements.